2019
DOI: 10.1093/mnras/stz3050
|View full text |Cite
|
Sign up to set email alerts
|

Angular momentum and heat transport on tidally locked hot Jupiter planets

Abstract: The atmospheric circulation in the upper atmosphere of hot Jupiter planets is strongly influenced by the incoming stellar radiation. In this work we explore the results from a 3D atmospheric model and revisit the main processes driving the circulation in hot Jupiter planets. We use the angular momentum transport as a diagnostic and carry out a Fourier analysis to identify the atmospheric waves involved. We find that the coupling between the angular momentum transported horizontally by the semi-diurnal tide and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 55 publications
3
34
0
Order By: Relevance
“…The fact that the majority of day-night heat transport is due to the divergent circulation, for both the terrestrial planet and the hot Jupiter, is an important result, as some previous work studying day-night heat transport on tidally locked planets has focused entirely on the role of the jet and stationary waves (43,51,52). The red line in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The fact that the majority of day-night heat transport is due to the divergent circulation, for both the terrestrial planet and the hot Jupiter, is an important result, as some previous work studying day-night heat transport on tidally locked planets has focused entirely on the role of the jet and stationary waves (43,51,52). The red line in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The assumed temperature profile in the deep part of the atmosphere is crucial to the chemistry, not only locally, but throughout the vertical extent of the atmosphere if quenched. However, unlike the 3D temperature structure at lower pressures, which can be relatively well constrained with a GCM, the deep thermal structure is often ill-constrained by GCMs, because it evolves very slowly (Carone et al 2020;Mendonça 2020;Wang & Wordsworth 2020;Showman et al 2020). This can result in temperature-profiles that are only partially converged, featuring a small thermal inversion in the deep ( ≈ 10 bar) layers (e.g.…”
Section: Temperatures In the Deep Atmospherementioning
confidence: 99%
“…Especially the deep atmospheric layers ( > 10 bar), which have a comparatively long radiative timescale, have been noted to evolve very slowly (e.g. Amundsen et al 2016), leading to impractically long computation time requirements (Wang & Wordsworth 2020;Mendonça 2020). Moreover, it has been shown that, in some cases, the deep atmospheric evolution can have a dynamical feedback on the observable atmospheric layers above (Carone et al 2020).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The agreement in jet structure is notable in view of the very different dynamical cores used in the two simulations and demonstrates that the use of the cube sphere grid has not distorted the relevant angular momentum transport processes, since the jet speed is sensitive to angular momentum transport (Mendonça 2020).…”
Section: Heng Et Al (2011) Benchmarkmentioning
confidence: 79%